Prenatal alcohol exposure and educational achievement in children aged 8-9 years - O'Leary, Colleen; Taylor, Catherine; Zubrick, Stephen; Kurinczuk, J.; Bower, C. (American Academy of Pediatrics, 2013)
Objective: This study examines the relationships between the dose, pattern, and timing of prenatal alcohol exposure and achievement in reading, writing, spelling, and numeracy in children aged 8 to 9 years. Methods: Data from a randomly selected, population-based birth cohort of infants born to non-Indigenous women in Western Australia between 1995 and 1997 (n = 4714) (Randomly Ascertained Sample of Children born in Australia’s Largest State Study cohort) were linked to the Western Australian Midwives’ Notification System and the Western Australian Literacy and Numeracy Assessment statewide education testing program. The records for 86% (n = 4056) of the cohort were successfully linked with education records when the children were aged 8 to 9 years. The associations between prenatal alcohol exposure and achievement of national benchmarks in school numeracy, reading, spelling, and writing tests and nonattendance for the tests was examined. Logistic regression was used to generate adjusted odds ratios (aOR) and 95% confidence intervals (CI), adjusting for potential confounding factors. The referent group included children of mothers who previously drank alcohol but who abstained during pregnancy. Results: Children were twice as likely not to achieve the benchmark for reading after heavy prenatal alcohol exposure during the first trimester (aOR 2.26; 95% CI 1.10–4.65) and for writing when exposed to occasional binge drinking in late pregnancy (aOR 2.35; 95% CI 1.04–5.43). Low-moderate prenatal alcohol exposure was not associated with academic underachievement. Conclusions: The type of learning problems expressed depends on the dose, pattern, and timing of prenatal alcohol exposure.